2008
DOI: 10.1007/s12032-008-9119-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a place for low-dose chest and prophylactic brain irradiation in limited-disease small cell lung cancer

Abstract: The aim of the study is to evaluate the outcome of low-dose bifractionated up-front radiotherapy (RT) followed by chemotherapy (CHT) in limited-disease small cell lung cancer (LD-SCLC). From December 1999 to February 2002, 20 LD-SCLC consecutive patients were treated by initial involved-field thoracic irradiation of 2 Gy twice daily to a total dose of 20 Gy, and concomitant prophylactic cranial irradiation (PCI) of 1.8 Gy twice daily to a total dose of 18 Gy followed 3 days later by 4-6 cycles of CHT with cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…All patients (100%) received HA-PCI to the prescribed total dose of 25 Gy. HA-PCI was administered over a median of 13 days (range, [11][12][13][14][15][16][17][18][19][20][21]. Eight patients had a treatment delay during treatment (toxicity in 2 patients, a deterioration of general condition in 1 patient, and technical reasons in 5 patients).…”
Section: Patients and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients (100%) received HA-PCI to the prescribed total dose of 25 Gy. HA-PCI was administered over a median of 13 days (range, [11][12][13][14][15][16][17][18][19][20][21]. Eight patients had a treatment delay during treatment (toxicity in 2 patients, a deterioration of general condition in 1 patient, and technical reasons in 5 patients).…”
Section: Patients and Treatmentmentioning
confidence: 99%
“…11 Two other phase 2 trials found similar results with the application of PCI before the start of chemotherapy in LD SCLC. 12,13 PCI may be associated with a decline in neurocognitive function (NCF), 10,14,15 and this needs to be weighed against the reduced incidence of brain metastases.…”
Section: Introductionmentioning
confidence: 99%